Near Vision but not Hearing Loss is Associated with Lacking a Usual Source of Health Care. (October 2021) - Simning, Adam; Caprio, Thomas V.; Li, Yue; Conwell, Yeates
Objectives: Sensory loss may be a barrier to accessing healthcare services, and this study seeks to examine the association of sensory loss with whether older adults report having a usual source of health care.Methods: Our study included 7548 older adults who participated in the National Health and Aging Trends Study in 2015. Having a self-reported usual source of health care was our outcome, and hearing and vision loss were our primary independent variables.Results: In multivariate analysis accounting for demographics, socioeconomic, health status, and environmental covariates, near vision loss but not distance vision or hearing loss was associated with decreased odds of having a usual source of health care.Discussion: That older adults with near vision loss were less likely to report having a usual source of health care is concerning. Examining barriers to care is needed to identify sensory loss-relevant processes to optimize and intervene upon.